Low-dissolved-oxygen nitrification in tropical sewage: an investigation on potential, performance and functional microbial community - How, Seow Wah; Lim, S.Y.; Lim, P.B.; Aris, A.M.; Ngoh, Gek Cheng; Curtis, Thomas Peter; Chua, Adeline Seak May (IWA Publishing, 2018)
Intensive aeration for nitrification is a major energy consumer in sewage treatment plants (STPs). Low-dissolved-oxygen (low-DO) nitrification has the potential to lower the aeration demand. However, the applicability of low-DO nitrification in the tropical climate is not well-understood. In this study, the potential of low-DO nitrification in tropical setting was first examined using batch kinetic experiments. Subsequently, the performance of low-DO nitrification was investigated in a laboratoryscale sequential batch reactor (SBR) for 42 days using real tropical sewage. The batch kinetic experiments showed that the seed sludge has a relatively high oxygen affinity. Thus, the rate of nitrification was not significantly reduced at low DO concentrations (0.5 mg/L). During the operation of the low-DO nitrification SBR, 90% of NH4-N was removed. The active low-DO nitrification was mainly attributed to the limited biodegradable organics in the sewage. Fluorescence in-situ hybridisation and 16S rRNA amplicon sequencing revealed the nitrifiers were related to Nitrospira genus and Nitrosomonadaceae family. Phylogenetic analysis suggests 47% of the operational taxonomic units in Nitrospira genus are closely related to a comammox bacteria. This study has demonstrated active low-DO nitrification in tropical setting, which is a more sustainable process that could significantly reduce the energy footprint of STPs.